(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Brutal killings of Christians in the northern and middle parts of Nigeria at the hands of Muslim militants and terrorists have been a daily occurrence in recent years. Nigeria daily news are always full of records of shielding of innocent bloods both adult and young, burning of Churches, the worst of them all is killings of Christian members during Church services. The major concerns now are days are kidnapping people after which the ransom will be paid and victim will eventually be killed. Increasingly, the attackers have included another group, militant nomadic Fulani herdsmen who raid villages and kill Christian men, women, children, and babies with, local weapon AK-47s, machetes and many others. This work considers the attitude of both the past and present administrations towards the brutal killings of Christian in the Northern part of the country it was equally linked with the story of Jesus Crucifixion and those that were supposed to speak and defended him master minded the killing of the Saviour of the entire universe. However, the work came out with the effect of the brutal killings, causes and concludes by suggesting the way out